A TiS2/Celgard separator as an efficient polysulfide shuttling inhibitor for high-performance lithium–sulfur batteries. Issue 48 (3rd November 2020) - Yan, Guanfusheng; Xu, Chuan; Meng, Zhaohui; Hou, Mingzhen; Yan, Wen; Lin, Naibo; Lai, Linfei; Zhan, Da
Abstract : In this work, we adopted a simple solid-phase sintering method to synthesize TiS2 and further modified the Celgard membrane by vacuum filtration, and found that the TiS2 -VF/Celgard membrane can restrain the shuttling effects of polysulfide. Abstract : The rapid capacity loss caused by the shuttling effect of polysulfides is one of the great challenges of Li–S batteries. In this work, we adopted a simple solid-phase sintering method to synthesize titanium disulfide (TiS2 ) and further demonstrated it as a superior modifier of separators for Li–S batteries. Two commonly adopted modification processes of separators, including vacuum filtration (VF) and slurry casting (SC) have been used to prepare TiS2 /Celgard separators. TiS2 -VF/Celgard can better restrain the polysulfide shuttling effect compared with TiS2 -SC/Celgard. A TiS2 -VF/Celgard-based Li–S battery has a reversible capacity of 771.6 mA h g −1, with a capacity retention of 645.6 mA h g −1 after 500 cycles at 2.0 C, corresponding to a capacity fading rate of ∼0.033% per cycle. This study has shown the potential of TiS2 as a multifunctional modifier of separators for high performance and long cycle life Li–S batteries.